Ninety-day complications after lung lobectomy and bilobectomy: A cohort single-center retrospective study - S. A. Prokopyev; A. Yu. Mironov (Кубанский научный медицинский вестник, 2025)
Background. Lobectomy is one of the most performed procedures in thoracic surgery. The fact that domestic literature does not provide an analysis of long-term outcomes after lobectomy and bilobectomy prompted us to conduct this study and identify factors that have a reliably negative effect. Objective. To evaluate postoperative complications occurring within 90 days after lobectomy and bilobectomy performed for malignant neoplasms and to identify their risk factors. Methods. The cohort single-center retrospective study included 277 patients who underwent open and thoracoscopic lung resection (lobectomy and bilobectomy) from January 2021 to December 2023 at the Surgical Oncology Department No. 3 of the Republican Clinical Oncology Center (Ministry of Health of the Chuvash Republic). The patients were divided into two groups: the first group (n = 232) comprised patients without complications, and the second group (n = 45) consisted of patients with complications. The overall postoperative case fatality rate within 90 days after the performed surgical procedure was evaluated. Hospital readmissions and all outpatient visits were analyzed. All clinical complications within 90 days after lobectomy and bilobectomy were recorded, and their risk factors were identified. The obtained results were statistically analyzed using Statistica 10 (StatSoft, USA). Results. The study analyzed 90-day postoperative complications in patients after lung resection (lobectomy and bilobectomy). The rate of complications amounted to 16.25% (45/277). Within 90 days after the procedure, the overall case fatality rate amounted to 6.5% (18/277), with the inpatient and posthospital case fatality rates reaching 1.81% (5/277) and 4.69% (13/277), respectively. In the present study, the hospital readmission rate was 7.22% (20/277), which is lower than in other known similar studies conducted abroad, where the reported values ranged from 9.3 to 24.8%. In the second group, patients predominantly had an ECOG2 performance status (Eastern Cooperative Oncology Group). The main risk factor for complications was the extent of surgery. Thoracotomy with rib resection and marginal pulmonary artery resection increased the rate of complications. Conclusion. The conducted study comprehensively analyzed the rate and composition of postoperative complications within 90 days after lobectomy and bilobectomy performed for malignant neoplasms. The key risk factors for complications were identified, which include marginal pulmonary artery resection and thoracotomy with rib resection, as well as ECOG status and the presence of complications of the primary disease (e.g., atelectasis and pneumonia). No effect of conventional parameters such as age, sex, and smoking was found on the rate of complications. The absence of significant differences in complication rates between thoracoscopic and open resection requires further study on larger samples of participants. The study results highlight the need for prospective studies aimed at a more in-depth analysis of postoperative complications and their risk factors